Effects of vitamin E, green tea polyphenols, and Ocimum gratissimum leaf essential oil as a supplement to extender on frozen-thawed canine sperm quality - Nguyen Van Vui; Samorn Ponchunchoovong; Sajeera Kupittayanant; Pakanit Kupittayanant (Veterinary Integrative Sciences)
During cryopreservation, oxidative stress is a principal cause of reducing the quality of frozen canine sperm. To prolong the longevity of canine sperm, adding vitamin E, green tea polyphenols, and Ocimum gratissimum essential oil in the semen extender was fulfilled to assess the effects of these antioxidant substances on frozen canine sperm quality. A total of twelve ejaculates were collected from three American Bully dogs in this study. The sperm straws were frozen in a programmable freezer at a freezing rate of 5°C/min from 4 to -15°C and 20°C/min from -15 to -100°C. The sperm motility, mitochondrial membrane potential, plasma membrane, and acrosome membrane integrity parameters were used to evaluate the quality of canine sperm using computer-assisted sperm analysis and confocal laser scanning microscope. The sperm lipid peroxidation was conducted using a Thiobarbituric acid assay. The results presented that the canine frozen-thawed sperm motility parameters in all the treatments showed no remarkable difference (P>0.05). In addition, although the antioxidant activity of the vitamin E and green tea polyphenols were higher than that of the Ocimum gratissimum essential oil, the value of mitochondrial membrane potential, plasma membrane, and acrosome membrane parameters of frozen-thawed sperm in the Ocimum gratissimum essential oil extender were higher than those in the rest extenders and had a noticeable difference compared to the control group (P<0.05). In conclusion, Ocimum gratissimum essential oil is superior to vitamin E and green tea polyphenols in protecting canine sperm during the process of freezing and thawing.